ANALISIS CELAH KEAMANAN APLIKASI WEB E-LEARNING UNIVERSITAS ABC DENGAN VULNERABILITY ASSESMENT - Arief Budiman; Syaiful Ahdan; Muhammad Aziz (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2021)
The development of information and communication technology today brings convenience to human life. One of the things that is growing quite rapidly is a web-based application. The proliferation of web-based applications is a challenge for web-based application developers in developing security aspects. Vulnerability Assessment of the E-Learning web application aims to detect vulnerabilities, describe vulnerabilities, assess vulnerabilities based on the Common Vulnerability Scoring System, and provide solutions. The research stages used were the Vulnerability Assessment and Penetration Testing Life Cycle. In looking for vulnerabilities in this study using the Home version of the Nessus Vulnerability Scanning. Based on the results of the vulnerability scanning, it was found low vulnerability, medium vulnerability, high vulnerability, and critical vulnerability. Each vulnerability certainly has a different impact on vulnerability, but on a critical vulnerability, namely the Elasticsearch Transport Protocol Unspecified Remote Code Execution has the most serious impact with a base score of 9.8, so the overall risk level on the Web E-Learning application is High. So it can be concluded that the E-Learning Web application at ABC University is said to be vulnerable, because it has a serious impact that affects Confidentiality, Integrity, and Availability of the E-Learning web application through its vulnerabilities. Therefore, ABC University must immediately make improvements and evaluations of the security of the E-Learning Web Application so that the risk of vulnerability in the E-Learning Web Application can be reduced.